Absent Jews and Invisible Antisemitism in Postwar Vienna: Der Prozeß (1948) and The Third Man (1949). (April 2017) - Silverman, Lisa
After the Second World War, using culture – such as theater, film, and writing – to promote Austria as a separate nation became a helpful strategy for Austrians and the Allied Forces alike. In this context, the role of Jews and Jewish difference in revising Austrian self-definitions was particularly fraught. Antisemitic prejudices persisted after the Holocaust, even though Austrian Jews were now largely absent. However, in the early postwar years, antisemitism was more likely to rear its head via code words or backhandedly, in efforts to deny its very existence. This article investigates the presence and consequences of this 'invisible' antisemitism in postwar Vienna by juxtaposing two films made at roughly the same time: Der Prozeß (1948), a film about antisemitism that takes place in a nineteenth-century village over 300 miles away and features only innocent rural Jews and diabolical antisemites, while The Third Man (1949) features an urban tale of the black market and poisoned children set in post-1945 Vienna that does not mention either Jews or the reasons for their absence. This comparison suggests that the simultaneous repression and evocation of Jewish difference that characterized the creation of culture in Vienna before the Holocaust persisted in the immediate postwar era.